2011
DOI: 10.1016/j.jri.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Maternal background strain influences fetal–maternal trafficking more than maternal immune competence in mice

Abstract: The objective of this study was to determine if fetal-maternal cell trafficking is affected by maternal immune competence and/or parental background strain using fluorescence-activated cell sorting (FACS). In our experience the sensitivity of FACS allows for the detection of 5 fetal in 107 maternal cells and assessment of cell surface phenotype. Wild-type C57BL/6J (n=18), FVB/NJ (n=15), and immunodeficient B6129S7-Rag1tm1Mom/J (n=16) female mice were mated to C57BL/6J males homozygous for the green fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…We have previously suggested that fetal cells in the maternal organs may be MSCs [35]. Earlier work from our laboratory showed expression of surface markers on fetal cells that were characteristic of MSCs [8,15]. Another group demonstrated the presence of fetal MSCs in the bones PRITCHARD ET AL.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We have previously suggested that fetal cells in the maternal organs may be MSCs [35]. Earlier work from our laboratory showed expression of surface markers on fetal cells that were characteristic of MSCs [8,15]. Another group demonstrated the presence of fetal MSCs in the bones PRITCHARD ET AL.…”
Section: Discussionmentioning
confidence: 95%
“…In humans, trophoblast deportation is hypothesized to be important for induction of immune tolerance to the fetus [32] and is elevated in pre-eclampsia [32,33]. Further evidence comes from previous work in our laboratory showing that allogeneic matings have more fetal cell trafficking [15], suggesting that fetal cell transfer during pregnancy is affected by genetic differences between the mother and fetus. It is possible that fetal cell microchimerism plays a role in the development of maternal immune tolerance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…At 36 th week of gestation, 100% of pregnant women have fetal cells in their circulation and after delivery and 30-50% of healthy women have detectable fetal cells in their blood from 4 weeks to decades after delivery [279,282] (Table 12). Interestingly, in mice maternal background strain and strain differences between the mother and father significantly affected fetalmaternal trafficking (both the number of fetal cells and the relative distribution of cell types in maternal organs) more than maternal immune competence [284].…”
Section: Diabeticsmentioning
confidence: 99%
“…Mouse studies have suggested that histocompatibility is a key player associated with higher levels of microchimerism [Bonney and Matzinger, 1997;, although recent studies have implied that maternal background strain may be more important [Fujiki et al, 2008b;Kallenbach et al, 2011]. Mouse studies have suggested that histocompatibility is a key player associated with higher levels of microchimerism [Bonney and Matzinger, 1997;, although recent studies have implied that maternal background strain may be more important [Fujiki et al, 2008b;Kallenbach et al, 2011].…”
Section: Factorsmodifyingthelevelofmicrochimerismmentioning
confidence: 99%